Extraction and Characterization of Cathepsin Inhibitor from Milkfish - Tati Nurhayati; Ruddy Suwandi; Syefri Rusyadi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Proteolytic enzyme is distributed acros all organism including fish. Cysteine proteases are the largest group of proteolytic enzyme. Lysosomal cathepsin, one of cysteine protease enzyme, cause softening and degradation of myofibril protein and it’s activity is regulated by endogenous inhibitors. The purposes of this study were to optimize the extraction cathepsin inhibitors from the skin, muscles, and viscera of fish, to partially purify the cathepsin inhibitors of selected sources, and to study the characteristics of the cathepsin inhibitor. The cathepsin inhibitor could be extracted from muscle fish and partially purified using ammonium sulfate of 70%. The purified cathepsin inhibitor had optimum temperature at 40°C and the optimum at pH 8. Metal ions decreased the activity of the protease inhibitor, except 1 mM of metal ion Mn2+ and Na+. Keywords: Cathepsin, characterization, partial purification, protease inhibitor